2020
DOI: 10.14802/jmd.20052
|View full text |Cite
|
Sign up to set email alerts
|

Update on Current Technologies for Deep Brain Stimulation in Parkinson’s Disease

Abstract: Deep brain stimulation (DBS) is becoming increasingly central in the treatment of patients with Parkinson’s disease and other movement disorders. Recent developments in DBS lead and implantable pulse generator design provide increased flexibility for programming, potentially improving the therapeutic benefit of stimulation. Directional DBS leads may increase the therapeutic window of stimulation by providing a means of avoiding current spread to structures that might give rise to stimulation-related side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 78 publications
(98 reference statements)
1
73
0
Order By: Relevance
“…The anti-geronic protein α-Klotho (referred to as Klotho), plays a potential role in delaying age-related declines in cellular and tissue function, which has generated considerable interest in targeting this protein for the treatment of agerelated neurodegenerative diseases. 1 Systemic exogenous elevation of Klotho enhances cognition and neural resilience in young, aging, and in vivo models of Parkinson's disease (PD). [2][3][4] Interestingly, in addition to age-related abnormalities, cognitive decline, and premature death, Klotho-deficient mice display nigrostriatal neurodegeneration, a hallmark of PD.…”
Section: Peripheral Klotho and Parkinson's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The anti-geronic protein α-Klotho (referred to as Klotho), plays a potential role in delaying age-related declines in cellular and tissue function, which has generated considerable interest in targeting this protein for the treatment of agerelated neurodegenerative diseases. 1 Systemic exogenous elevation of Klotho enhances cognition and neural resilience in young, aging, and in vivo models of Parkinson's disease (PD). [2][3][4] Interestingly, in addition to age-related abnormalities, cognitive decline, and premature death, Klotho-deficient mice display nigrostriatal neurodegeneration, a hallmark of PD.…”
Section: Peripheral Klotho and Parkinson's Diseasementioning
confidence: 99%
“…and 2011, the company replaced the original IPGs with new ones, the ActivaPC and ActivaSC. Although the marketed lifespan of the batteries of the new brands was advertised as being longer than the older ones, 1 several studies eventually reported that the lifespan of the newer IPGs was in fact significantly shorter than that of its predecessors (Supplementary Table S1). This has been questioned by the company.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are three manufacturers with approved devices in the USA [117,118]. Medtronic was approved for use in PD in 2002, the Abbott Infinity system was approved in 2016 followed by the approval of the Boston Scientific Vercise system.…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…1, Table 1). 3,4 These advances have come with a price: programming has become even more complex, 5 emphasizing even more the need for a structured approach (Table 2).…”
Section: Deep Brain Stimulation (Dbs) Is a Well-established Treatment Formentioning
confidence: 99%